2017
DOI: 10.5194/acp-17-10709-2017
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric processes affecting the separation of volcanic ash and SO<sub>2</sub> in volcanic eruptions: inferences from the May 2011 Grímsvötn eruption

Abstract: Abstract. The separation of volcanic ash and sulfur dioxide (SO 2 ) gas is sometimes observed during volcanic eruptions. The exact conditions under which separation occurs are not fully understood but the phenomenon is of importance because of the effects volcanic emissions have on aviation, on the environment, and on the earth's radiation balance. The eruption of Grímsvötn, a subglacial volcano under the Vatnajökull glacier in Iceland during 21-28 May 2011 produced one of the most spectacular examples of ash … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 81 publications
(112 reference statements)
4
38
1
Order By: Relevance
“…This is also reflected in the ashfall deposition values, as a background value of ∼ 1-10 g m −2 mo −1 was also seen independently of the season and dominant wind patterns. Separation of SO 2 and volcanic ash is known to occur depending on the volcanological and meteorological conditions during an eruption (Prata et al, 2017). Even though previous studies focusing on volcanic emissions from Sakurajima have noted a high correlation between the concentrations of SO 2 and SPM after large eruptions Hillman et al, 2012;Sakamoto and Kinoshita, 2015), evidence shown here suggest that this correlation is weaker for long-term dispersal and holds true mainly for stations close to the volcano.…”
Section: Discussioncontrasting
confidence: 45%
“…This is also reflected in the ashfall deposition values, as a background value of ∼ 1-10 g m −2 mo −1 was also seen independently of the season and dominant wind patterns. Separation of SO 2 and volcanic ash is known to occur depending on the volcanological and meteorological conditions during an eruption (Prata et al, 2017). Even though previous studies focusing on volcanic emissions from Sakurajima have noted a high correlation between the concentrations of SO 2 and SPM after large eruptions Hillman et al, 2012;Sakamoto and Kinoshita, 2015), evidence shown here suggest that this correlation is weaker for long-term dispersal and holds true mainly for stations close to the volcano.…”
Section: Discussioncontrasting
confidence: 45%
“…This study addresses the three Icelandic volcanoes that were active during the 19-year period covered by the NASA Earth Observing System (EOS) to date. Detailed discussion of the individual eruptions have previously been published for: Eyjafjallajökull 2010 (e.g., Arason et al, 2011;Cioni et al, 2014;Gudmundsson et al, 2012;Kahn & Limbacher, 2012;Sigmarsson et al, 2011;Sigmundsson et al, 2010), Grímsvötn 2011 (Moxnes et al, 2014;Petersen et al, 2012;Prata et al, 2017), and Holuhraun 2014-2015 • Remote sensing observations of Icelandic eruptions distinguish different types of volcanic emissions • Evidence of downwind aerosol formation, particle hydration, and possible activation were identified in Icelandic plumes • Variations in derived particle proxies in ash-rich plumes correlate with changes in eruptive processes and magma composition Supporting Information:…”
Section: Introductionmentioning
confidence: 99%
“…As this ice-rich region evolved, the ash-rich portion of the cloud drifted westwards, with a clear separation of the two parts of the eruption cloud. Separation of constituents in eruption clouds has been noticed and discussed previously [71] in the context of ash and SO 2 gas separation for the May 2011 eruption of Grímsvötn in Iceland. Ice and ash separation has not been previously reported in the literature.…”
Section: Volcanic Icementioning
confidence: 82%
“…The case study for the volcanogenic ice and ash from the eruption of Sinabung, Indonesia illustrates a new feature of complex mixed-constituent volcanic clouds: separation of ice-rich and ash-rich portions of the eruption clouds. Previous work [71,83] has shown that volcanic SO 2 and ash can travel together or undergo maximum separation, and separation of ice and ash clouds in the 2005 Manam eruption can be seen in [63] but the process is not elaborated. The separation of ice-rich and ash-rich portions of volcanic clouds and indeed of SO 2 -rich portions, has important consequences for dispersion modelling and forecasting volcanic hazards to aviation.…”
Section: Discussionmentioning
confidence: 99%